Impact of modified industrial wet processing stages on the quantity and quality of Nile perch (Lates niloticus) oil extracted from the visceral organs - Otieno, Dennis; Hilda, Nyaboke; Odoli, Cyprian; Nyamweya, Chrisphine; Christopher, Aura (My University, 2019)
Global fish oil production is between 1 to 1.25 million tonnes and primarily exploiting fatty fish such as menhaden, herring, pilchards, anchovy, and sardine among others. The main producing countries include Japan, USA, Chile and Peru. Yet, fish oil from developing countries end up as bio waste since only the flesh is utilized. This paper discusses a simple approach for utilizing the fish bio waste to produce oil and how the oil quality and quantityis impacted by the extraction process. The visceral organs were collected from fish filleting factory and markets in Kisumu town and oil extracted by modified wet pressing method adopted from Blight and Dyer (1959). The effect of temperature and serial washing on the oil quality and quantity was assessed from extraction temperatures at 800C, 900C, 950C and 970C, while employing three serial washing using distilled water and pineapple juice. The quality of the oil produced was then determined based on the proportion ofomega -3, vitamin A and E, peroxide value, iodine value and free fatty acids. Results indicate that maximum extraction efficiency was achieved at 800C for 30 minutes where 156.05g of oil was extracted, when compared to 155.32g at 90ºC,155.24g at 95ºC,155.23g at 97ºC from a tissues of 171.25gin each case. The data was then analyzed using ANOVA at P<0.05 and post hock to determine significance. It was concluded that the temperature manipulation procedures as per this study was reliable to produce maximum yield and can be adopted by oil producing plants.
Keywords: Fish Oil; Nile perch; omega 3; waste to resources